Bond-slip performance of GFRP and steel reinforced beams under wet-dry and freeze-thaw cycles: The effect of concrete type. (1st August 2022) - Shakiba, Milad; Bazli, Milad; Karamloo, Mohammad; Mohammad Reza Mortazavi, Seyed
Highlights: Bond-slip durability of GFRP reinforced concrete beams under wet-dry and freeze-thaw cycles were studied. Flexural pull-out beam test was used. Normal, self-compacting, and fibre-reinforced concretes were studied. Steel and GFRP reinforced beams were compared. Abstract: In this experimental study, the bond-slip performance between glass fibre reinforced polymer (GFRP) bars and three different concrete types, namely normal, self-compacting, and fibre-reinforced concrete under freeze-thaw and wet-dry cycles have been studied. Steel reinforced concrete beams were also tested for comparison purposes. In total, 54 GFRP and steel reinforced concrete beams were prepared, conditioned, and tested using RILEM recommendations. 18 specimens were subjected to 200 wet-dry cycles between ambient and 60 ˚C and another 18 specimens were subjected to 200 freeze-thaw cycles between -18 ˚C and 4 ˚C for 150 days. The results showed the bond strength reductions of 12, 3 and 9 % between steel bars and beam specimens cast with normal, self-compacting, and fibre-reinforced concrete, respectively after exposure to 200 wet-dry cycles. However, the corresponding values for GFRP reinforced concrete beams under the same conditioning environment were 1, 1, and 16 % respectively. With respect to freeze-thaw cycles, bond strength of steel reinforced normal, self-compacting, and fibre-reinforced concretes experienced only about 5, 2, and 4 % reductions, respectively, after 200 cycles. The corresponding reduction values for GFRP reinforced beams were insignificant and about 2, 1, and 4%. Steel reinforced beams fail due to the concrete crushing, while GFRP reinforced beams fail due to GFRP surface peeling-off. Generally, GFRP reinforced beams experienced fewer bond strength reductions compared to steel reinforced beams. Also, regardless of concrete type, due to their corrosion vulnerability, steel reinforced beams experienced greater stiffness reductions than that of GFRP reinforced beams when subjected to seawater wet-dry cycles. However, such a difference was not drastic.